ANALISIS KINERJA INDUSTRI MANUFAKTUR DI JAWA TENGAH: APLIKASI DEA MODEL VRS - Samudro, Bhimo Rizky; Pratama, Yogi Pasca (eBA Journal: Journal Economics, Bussines and Accounting, 2018)
This study aims to estimate the level of efficiency of the manufacturing industry in Central Java Province. The position of the manufacturing industry in Central Java between two clusters of Jakarta-Bandung and Surabaya were the justification for the urgency of this research. The concept of relative efficiency with format Constant Return to Scale (CRS) and the Variable Return to Scale (VRS) was used as the theoretical framework of this research. The concept was applied by the method of Data Envelopment analysis (DEA) to describe the level of efficiency of the manufacturing industry sub-sector in Central Java province in 2016. The study also describes a way of increasing efficiency in production output for the manufacturing sub-sector classified as inefficient. DEA model used in this study is the CRS and VRS with the orientation of the output (output-oriented)The results of this study indicate that the apparel sub-sector; wood and processing; machinery and equipment; as well as furniture and processing is a sub-sector of manufacturing industry in Central Java in 2016 were classified as inefficient. Sub sectors using too much input unit, thus creating inefficient production levels relative to other sub-sectors.